A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF MTS HUBBULWATHAN DURI IN WRITING RECOUNT TEXTS - Annisa, Nurul; Eliwarti, Eliwarti; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This quantitative descriptive study aims to find out the students' ability in writing recount text. The sample of this study was 27 students of class VIII 1 MTs Hubbulwathan Duri. This research used cluster random sampling technique. The instrument used written test in which students wrote their own recount text according to a theme that has been determined by the writer. In analyzing the data, it had done by calculating the scores of students individually and looking for the average scores. As for the results obtained from this study, the ability of eighth graders in writing recount text is in the good category with an average of 80.36. The results for each aspect are very good for aspects of content (89.66), organization (91.33), vocabulary (86.66), while good for aspects of grammar (83.66) and mechanics (79.33). Based on these results, it is suggested for students to be able to practice writing skills by frequently reading and writing journals. As for the teacher, it is being able to make recount text writing lessons more fun so that students do not get bored in writing. For the researchers, It is recommended that researchers make this research a reference and can focus more on every aspect of writing, especially in the mechanics aspect.Key words: Writing, Recount Text, Ability, Quantitative